Block‐Copolymers Enable Direct Reduction and Structuration of Noble Metal‐Based Films. Issue 5 (25th November 2021) - Gayrard, Maxime; Chancerel, Francois; De Marco, Maria Letizia; Naumenko, Denys; Boissière, Cédric; Rozes, Laurence; Amenitsch, Heinz; Peron, Jennifer; Cattoni, Andrea; Faustini, Marco
Abstract: Noble metal nanostructured films are of great interest for various applications including electronics, photonics, catalysis, and photocatalysis. Yet, structuring and patterning noble metals, especially those of the platinum group, is challenging by conventional nanofabrication. Herein, an approach based on solution processing to obtain metal‐based films (rhodium, ruthenium (Ru) or iridium in the presence of residual organic species) with nanostructuration at the 20 nm‐scale is introduced. Compared to existing approaches, the dual functionality of block‐copolymers acting both as structuring and as reducing agent under inert atmosphere is exploited. A set of in situ techniques has allowed for the capturing of the carbothermal reduction mechanism occurring at the hybrid organic/inorganic interface. Differently from previous literature, a two‐step reduction mechanism is unveiled with the formation of a carbonyl intermediate. From a technological point of view, the materials can be solution‐processed on a large scale by dip‐coating as polymers and simultaneously structured and reduced into metals without requiring expensive equipment or treatments in reducing atmosphere. Importantly, the metal‐based films can be patterned directly by block‐copolymer lithography or by soft‐nanoimprint lithography on various substrates. As proof‐of‐concept of application, the authors demonstrate that nanostructured Ru films can be used as efficient catalysts for H2 generation into microfluidic reactors. Abstract : Noble metal‐based films, nanostructured at the 20 nm‐scale, are obtained by solution processing by exploiting the dual functionality of block‐copolymers as structuring and reducing agents. A multitechnique in situ study has allowed capturing the reduction/structuring mechanism. This approach is compatible with large scale patterning by nanoimprint lithography and enables easy integration of nanostructured metallic films into microfluidic reactors.